POLICY IMPLEMENTATION EVALUATION OF THE TRAINING MANAGEMENT OF RIAU ISLANDS PROVINCE’S TRAINING CENTER - Madsihit Madsihit; Moch. Asmawi; R. Madhakomala (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
This study aims to evaluate the implementation of the training management of Riau Island Province’s Training Center. This study used a qualitative approach, which uses a model discrepancy which includes four stages: (1) design, (2) installation, (3) process, and (4) product. In the data collection is done through observation, in-depth interviews and documentation study. Interviews were conducted to business and policy makers at the Training Center of Riau Islands province, trainees and other stakeholders. The results of this study concluded that based on the discrepancy evaluation, the implementation of the training management of Riau Island Province’s Training Center, although in terms of policy implementation designation (design) and the preparation of implementation (installation) is quite good, but the execution (process) can not run properly so that the achievements results (product) is not satisfactory. Keywords: Training management, training and discrepancy